Research and Evaluation of a Cyberchondria Severity Scale in a Chinese Context - Wang D; Sun L; Shao Y; Zhang X; Maguire P; Hu Y (Psychology Research and Behavior Management, 2023)
Dawei Wang,1 Lingchao Sun,1 Yunru Shao,1 Xiaoyan Zhang,1 Phil Maguire,2 Yixin Hu1 1School of Psychology, Shandong Normal University, Ji’nan, Shandong, People’s Republic of China; 2Department of Computer Science, National University of Ireland, Galway, IrelandCorrespondence: Yixin Hu, School of Psychology, Shandong Normal University, Jinan, Shandong Province, 250358, People’s Republic of China, Email huyixin2005@163.comPurpose: Cyberchondria is a problematic or unhelpful behavior pattern that describes excessive or repetitive online health-related information searching related to an enhanced level of health anxiety. Such internet-derived medical anxiety can manifest itself in different ways across cultures. This study explores the unique nature of cyberchondria in the context of Chinese culture, identifying the risk factors for the condition and the possible negative outcomes.Methods: An exploratory factor analysis (EFA) was used to explore whether the structure of the Chinese version of the Cyberchondria Severity Scale (C-CSS) is different from that in western context. Subsequently, a confirmatory factor analysis (CFA) was used to verify the model fit of the C-CSS. Finally, a series of regression analysis were used to test the relationship between cyberchondria and its antecedent variables and consequence variables in Chinese context.Results: Retained 18 items and revised to 3 dimensions (Negative Effects, Excessiveness and Reassurance Seeking), the Chinese version of the Cyberchondria Severity Scale (C-CSS) was developed. In the context of China, the three antecedents were also effective predictors of cyberchondria, and C-CSS is also related to theoretically relevant outcomes.Conclusion: This study initially demonstrated the validity, reliability and applicability of C-CSS to assess the severity of cyberchondria among Chinese undergraduates.Keywords: cyberchondria severity scale, medical anxiety, Chinese health system, validity, reliability